Habilidades inferenciais no desenvolvimento escolar: um trabalho com o gênero “tirinha” - Soraia Aparecida de Pinho Cunha Ferreira (2020)
The present research work has the objective of developing a literacy project, from the reading of humorous texts of the comic strip genre and of the work with a didactic project of this genre, so that the 6th year elementary school student develops skills and abilities making inferences. This choice is justified by the students' interest in reading this genre. Usually, they open the books and browse through them looking for some comic strip, comic book, cartoon or cartoon. Therefore, it is noted that the interest in texts with non-verbal language is great. Another reason is the increasing presence of this textual genre in the textbook and in external tests. The objective of the research is to seek ways for the student to improve his reading competence, not only to read comic strips, but also other textual genres. Within the process of reading and understanding text, the proficient reader performs important operations, one of which is inference. It constitutes a process that is activated during the reading of the text. The work proposed here was developed aiming at a teaching proposal aimed at developing skills to make inferences in the genres of humor, especially the comic strip, with a view to improving the competence of interpreting texts. For that, it is necessary to deal with conceptions of language, reading, inferences, genres of speech, humor, multimodality, assumptions and inferences, etc. The theoretical basis presented here is based, mostly, on J. L. Fiorin (2011 E 2017), M. Bakhtin (2016), M. Soares (2017), R. P. Dell’Isola (2001), A. A. Faria (2017), I.G.V. Koch and V.M. Elias (2017), B. A. Cunha (2018), A. Kleiman (2002), among others. The theme of the strips selected for the teaching plan - work and consumption - is based on the National Curriculum Parameters and the Common National Curriculum Base. This research was carried out in two classes of the 6th year of elementary school at the Escola Estadual Fazenda São Sebastião, located in Guanhães, a city in the interior of Minas Gerais. To carry out this work, an initial questionnaire, a teaching plan with various reading and analysis activities and comic strips and a final test were applied. The activities of the reading and text interpretation workshops stimulated students to understand the text and to detect the humor present in it. The results of this research show that it is necessary to work with the theme "work and consumption". Another conclusion of the research is that the students need to be guided to read the images and make the pertinent inferences. It was noticed the students' evolution to each applied activity and to each return and comment on it. Therefore, inferential skills can be worked on and developed in the comic strip genre.